The Influence of Tax System Modernization, Public Trust, and Taxpayer Awareness on Tax Compliance - Tsaninda Adzkya Azleany Azreen; Kurnia (Amkop Management Accounting Review (AMAR), 2025)
This research endeavors to scrutinize how enhancements to the taxation system, citizens' faith in governance, and comprehension among taxpayers impact the adherence to tax regulations by self-employed individual taxpayers within the jurisdiction of the Cianjur Pratama Tax Office. A quantitative methodology is employed, characterized by a descriptive causal investigation framework. The entire demographic under consideration encompasses all self-employed individual taxpayers duly registered at the Cianjur Pratama Tax Office, which amounts to 75,350 individuals; a subset of 100 participants was chosen utilizing a convenience sampling technique. Information was gathered via questionnaires employing a five-tiered Likert scale in conjunction with supplementary information extracted from authorized Directorate General of Taxes records. Evaluations pertaining to accuracy and consistency were performed to ascertain the tool's appropriateness for deployment. Analytical procedures were executed utilizing IBM SPSS Statistics 26, encompassing descriptive statistical assessments and evaluations of fundamental assumptions, specifically normality, multicollinearity, and heteroscedasticity), multiple linear regression, and hypothesis testing with t-tests, F-tests, and coefficients of determination (R²). The results show that tax system modernization, public trust, and taxpayer awareness partially and simultaneously have a positive and significant effect on the compliance of non-employee WPOP. These findings emphasize the importance of system modernization, increased trust, and tax education as effective strategies to improve taxpayer compliance.